Determination of taurine in soft drinks by an ultrahigh-performance liquid chromatography-mass spectrometry method - Chalova P.; Salaskova D.; Csicsay F.; Galba J.; Kovac A.; Piestansky J. (Sciendo, 2023)
Taurine (2-aminoethanesulfonic acid) is a free sulfur-containing β-amino acid widely distributed in many mammalians. Owing to the energizing effects, it is mostly used in soft drinks and supplements for athletes. Regular intake of soft drinks may lead to an overdose of caffeine, taurine, and guarana and loss of bone mass, overweight, hypertension, and in older age, osteoporosis and cardiovascular diseases. Therefore, it is essential to control the maximum amount of taurine consumed by humans in the food and beverages. Here, a fast, simple, accurate, and robust method based on ultrahigh-performance liquid chromatography hyphenated with mass spectrometry (UHPLC-MS) was successfully applied for the determination of taurine in selected soft drinks sold in Slovakia. The method was characterized by coefficient of determination higher than 0.99, and the predicted value of the limit of detection was 4.29 μmol/L. The analyzed levels of taurine in selected commercial drinks ranged from 2.8 to 3.78 mg/mL. The concentration in one brand of the investigated drinks was found to be extremely low (about 70%) compared to the declared content by the manufacturer.